Effectiveness of the Design Platform Canva on the Creative Thinking of Visual Communication Design Students - Ramdani Abdul Malik; Ramanda Dimas Surya Dinata; Freddy Hendrawan (Gorga : Jurnal Seni Rupa, 2025)
Technology has penetrated the creative industry, particularly in the Visual Communication Design sector, particularly in the field of visual design tools. One clear example of this technological advancement is the Canva instant design platform. Canva has become a widely used design application due to its user-friendly design features. Therefore, this study aims to analyze the influence and impact of instant design platforms, specifically Canva, on the creative thinking skills of Visual Communication Design (DKV) students. Data collection was conducted through an experimental method involving 30 respondents. Respondents were divided into two groups: users of the Canva instant design platform and users of the Adobe family of conventional design platforms. Based on the results of the data processing and experiment, it can be concluded that the Canva instant design platform has a significant impact on students' creative thinking patterns, particularly in terms of fluency in expressing ideas visually. The findings indicate that Canva users tend to have higher creative thinking scores than Adobe users, with average scores in the moderate creative range. Assessment was conducted using a creative thinking rubric with five main indicators: fluency, originality, elaboration, symbolism, and flexibility.